Implementasi Firefly Algorithm untuk Optimasi Produksi Pakaian di Edmee Outfit Bondowoso - Zogie Lestary (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Proper production planning is an important factor for Small and Medium Enterprises (SMEs) in maximizing profit while operating under limited resources. Edmee Outfit Bondowoso, a garment manufacturing company, faces challenges in determining optimal production quantities for each clothing product due to limitations in raw materials, machine capacity, and production costs, as well as fluctuating market demand. This study aims to determine the optimal production combination using the firefly algorithm. The data used in this study are primary data obtained directly from Edmee Outfit during the December 2025 production period, including raw material availability, machine capacity, production costs, selling prices, and product demand. The production problem is first formulated into a linear programming model to maximize profit. The model is then solved using the firefly algorithm, implemented in Python. Parameter tuning is conducted to determine the optimal algorithm configuration based on profit, convergence behavior, and computational time. The results show that the firefly algorithm generates an optimal production plan with a maximum profit of Rp217,230,000 per production period and a total output of 2,975 units. The best parameter configuration is obtained at n = 125, α = 0.3, γ = 0.001, β₀ = 1.5, and Imax = 500. In addition, the utilization of production resources remains within optimal limits without exceeding existing constraints. Therefore, the firefly algorithm proves to be an effective decision-support tool for optimizing garment production planning at Edmee Outfit Bondowoso.
Finalisasi Rudy K
Keywords: production optimization; firefly algorithm; linear programming; SMEs; garment industry